The Application of Benson Relaxation Techniques as a Stress Management Strategy for Posyandu - Essa Andaru Anugraheni; Arum Pratiwi; Tri Setianingsih (Jurnal Keperawatan Profesional, 2026)
Stress among public health volunteers, such as Posyandu workers, can lead to a decline in service quality and community involvement. This study aims to investigate the effectiveness of the Benson relaxation technique in improving stress management among Posyandu workers. The method used in this study was a pre-experimental design with a pretest-posttest approach. The participants in this study were five active Posyandu officers. The intervention consisted of stress management lectures and practice of the Benson relaxation technique to control stress. The Benson relaxation technique was conducted for 20 minutes over three sessions. Data were collected using the Perceived Stress Scale (PSS-10) and analyzed descriptively and inferentially. The results showed a consistent decrease in the average stress score from 25.2 ± 1.9 (pretest) to 15.2 ± 1.9 (posttest). Participants reported increased calmness, emotional stability, better sleep quality, and greater confidence in carrying out public health tasks. The combination of physiological relaxation, spiritual affirmation, and social support contributed to the observed improvements. The conclusion drawn is that Benson relaxation education effectively reduces perceived stress and enhances psychological resilience among officers. This method is recommended as a nursing modality therapy that is accessible, low-cost, and sustainable for strengthening the mental health and performance of public health volunteers.